PENGALAMAN KERJA PERAWAT DALAM MERAWAT PASIEN DI RUANG ICU RSUD. Dr. PIRNGADI KOTA MEDAN - Anwari, Putri; Fitrini, Fitriani; Ramud, Suci Munawarah; Hasibuan, Eva Kartika; Purba, Bunga Theresia (Program Studi Ners UNIVERSITAS SARI MUTIARA INDONESIA, 2018)
Intensive Care Unit (ICU) is the last gate of hospital patients, especially patients who use ventilator and ICU need 24 hour monitoring. Nurses working in the Intensive Care Unit must be fast and precise, continuous work, high workload, less modern tools and family conditions can stress the consequences of nurse work and other health teams are not fluent and empathy for patients is decreasing, so that nursing care is given partially implemented and addressed on physical issues. This study aims to explore the work of nurses in caring for patients in the ICU. This research was conducted at ICU Pirngadi General Medan. The type of research used was qualitative with phenomenology approach, the participants in this study were nurses ICU which amounted to 4 people. Technique of taking participant in this study by way of purposive sampling. The results in this study have six themes, namely physical, nursing care, psychology, environment, facilities and expectations. The conclusion in this research is nurses tend to experience various problems in work so that nurses become less maximal in work it will affect service in ICU less maximal. Suggestion in this research is expected to nurse to maximal and discipline in work and to hospital service to pay more attention nurses work load by increasing knowledge and held training, addition of award to create maximum service.